A Case of Fatal Electrocution in Rural Nepal - Atreya, Alok; Thapa, Jagat Bahadur; Menezes, Ritesh G; Nepal, Samata; Nepal, Binu (Journal of Nepal Health Research Council, 2021)
Although preventable, electrocutions have claimed many lives in Nepal. People of low socio-economic background from remote villages in Nepal who visit jungle to tend cattle, collect firewood and cattle fodder are vulnerable to electrocution when the foliage are in contact with the power lines. We present a case of a 11-year-old boy who was found suspended over three naked high-tension electric wires approximately 30 feet above the ground in rural Nepal. This article describes a case of fatal electrocution and attempts to explain a reasons for such mishaps in Nepal through consideration of topography and socioeconomic factors. This article further discusses the death scene investigation in such cases. Keywords: Death scene investigation; fatal electrocution; high-tension transmission